2020
DOI: 10.1149/09810.0453ecst
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Metallic Materials in the Molten FLiNaK

Abstract: Corrosion resistance of molybdenum, tantalum, and nickel-based alloys was studied in molten salt systems based on LiF–NaF–KF mixture in the temperature range 550–750°C. The rates of corrosion of these materials were determined, the nature of the degradation of the surface of materials established, and the effect of the salt medium and temperature on the corrosive properties of metals and nickel-based alloys considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…During the reductive extraction step, the construction materials contact both liquid Bi-Li alloy and molten fluoride salt, and the choice of objects for the present study reflects this circumstance. Previously [20], we showed that molybdenum and nickel super alloys have high corrosion stability in fluoride melts; therefore, these metals were now selected for assessing their corrosion behavior in a Bi-Li alloy.…”
Section: Introductionmentioning
confidence: 99%
“…During the reductive extraction step, the construction materials contact both liquid Bi-Li alloy and molten fluoride salt, and the choice of objects for the present study reflects this circumstance. Previously [20], we showed that molybdenum and nickel super alloys have high corrosion stability in fluoride melts; therefore, these metals were now selected for assessing their corrosion behavior in a Bi-Li alloy.…”
Section: Introductionmentioning
confidence: 99%